2012
DOI: 10.4172/2153-2435.s15-001
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of Medical Malaysian Leech Saliva Extract (LSE)

Abstract: Leech saliva contains biologically active compounds that are mainly proteins & peptides. Small cell lung cancer (SCLC) is a form of cell lung carcinoma. In this study a modified and smooth extraction method of saliva was used without leech scarification. Trying to find out the biological activity of medical Malaysian Leech Saliva Extract as cytotoxic in vitro, the SW 1271 cell line was grown and maintained in Leibovitz ' s L-15 medium supplemented with 10% foetal bovine serum at 37°C in normal atmospheric air.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Previously, published data provided evidence that Shui Zhi could benefit cancer therapy by inhibiting the proliferation of human HepG2 and DNA methylation [ 1 ]. Other reports clearly showed that peptides from anticoagulant proteins, such as hirudin and antistasin aforementioned, were metastatic inhibitors against various cancers [ 56 , 57 ]. Since coagulation is related to proliferation and metastasis, blocking the cascade can have an antitumor effect [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, published data provided evidence that Shui Zhi could benefit cancer therapy by inhibiting the proliferation of human HepG2 and DNA methylation [ 1 ]. Other reports clearly showed that peptides from anticoagulant proteins, such as hirudin and antistasin aforementioned, were metastatic inhibitors against various cancers [ 56 , 57 ]. Since coagulation is related to proliferation and metastasis, blocking the cascade can have an antitumor effect [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it was observed that the combination of leech saliva with anticancer drugs decreased significantly the cell viability and cell migration in the SW1721 cell line compared with the application of anticancer drugs alone. 25 In the study by Pang et al, the effect of hirudin obtained from leech saliva on diabetic mouse kidney glomerular endothelial cell with renal angiopathy was investigated. 26 Hirudin applied to the glomerular endothelial cell line of diabetic mice with angiopathy was found to inhibit cell migration in an in vitro wound model.…”
Section: Discussionmentioning
confidence: 99%
“…to estimate the total proteins in Leech saliva extract. [ 26 ] Traditionally, in vitro determinations of toxic effects of unknown compounds have been performed by counting viable cells after staining with a vital dye.…”
Section: Discussionmentioning
confidence: 99%